Grub paʼi mthaʼi rnam par bźag pa rin po cheʼi ʼphreṅ ba - Vjigs-med-dbang-po (Kan-suʼu mi rigs dpe skrun khaṅ, 1995)
Concise explanation of the philosophical positions (siddhānta) of the Vaibhāṣika, Sautrāntika, Yogācārya, and Mādhyamika schools of Buddhism with Hinduism